The meaning of effective soil parameters for determining of the bearing capacity of cohesive soils - Wilk, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the analysis of the bearing capacity of cohesive soils, which was calculated based on the PN-EN-1997-1 methodology. This computations take into account the effect of pore water pressure on the soil strength parameters. The parameters for calculating the strength of the soil can be determined by direct tests (triaxial apparatus) or by indirect methods. Used in the previous norm PN-81/B-03020 correlations of physical parameters and strength parameters relate to the total stress. They do not include, what part of the stress is carried by an increase the pore water pressure, and what part acts on the soil skeleton. The problem of dispersion efficiency of excessive the pore water pressure during load relates in particular the soils with the fine particle sizes - cohesive soils. There is no defined dependencies, which can be used in indirect determining the bearing capacity of cohesive substrate according to PN-EN-1997-1.